Analisis Faktor-Faktor YangMempengaruhi Tingkat KemiskinanKota Semarang Tahun 1996-2014 - Murthy, Septian Adhi; , Drs. Yuni Prihadi U., MM (2017)
This study aimed to analyze the effects of inflation, the GDP and unemployment to poverty Semarang years 1996-2014. The data used in this research is secondary data. The analytical method used in this research is Ordinary Least Squares (OLS) to determine the direction and magnitude of the effect of an independent variable (independent) on the dependent variable (dependent). Based on the test results influence, obtained results that the significance level of 0.10 summed inflation variable has a positive impact on poverty with a coefficient of 0.067, the GDP variable has a negative and significant impact on poverty with a coefficient of -1078, while the unemployment variable has a negative and significant impact against poverty with a coefficient of -7568.